Pengaruh Profitabilitas dan Kesempatan Investasi terhadap Kebijakan Dividen: Studi Empirik pada Emiten Pembentuk Indeks LQ45 di Bursa Efek Indonesia - Elyzabet Indrawati Marpaung; Bram Hadianto (Jurnal Akuntansi, 2009)
The purpose of this research is to find the impact of profitability and investment opportunity on dividend policy. In this research, Sales Growth (SG) and Market To Book Value Ratio (MTBV) are proxies of the investment opportunity. Purposive sampling is used as sampling technique. The sample is taken from LQ45 index constituent company for year of 2004 until 2006. In this period, every company must pay dividend consistently. The polled data regression model is conducted as method of analysis. The results state that profitability and market to book ratio have positive impact on dividend policy. Sales growth has no impact on dividend policy. Keywords: profitability, market to book value ratio, dividend policy.